2017
DOI: 10.1136/bmjgast-2016-000129
|View full text |Cite
|
Sign up to set email alerts
|

Is there a standard for surgical therapy of hepatocellular carcinoma in healthy and cirrhotic liver? A comparison of eight guidelines

Abstract: Background and aimsLiver resection (LR) and transplantation are the most reliable treatments for hepatocellular carcinoma (HCC). Aim was to compare different guidelines regarding indication for resection and transplantation because of HCC with and without underlying cirrhosis.MethodsWe compared the following guidelines published after 1 January 2010: American (American Association for the Study of Liver Diseases (AASLD)), Spanish (Sociedad Espanola de Oncologia Medica (SEOM)), European (European Association fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…85 In patients without significant fibrosis, resection is universally advised as first-line treatment, but in patients with compensated cirrhosis, recommendations are mixed and vary by tumor size and number. 86 In patients otherwise eligible for LT, postresection 5-year recurrence-free survival is 40%-50%. 87,88 While 10-year overall survival is better with LT for resectable HCC, 89 many studies have shown similar 5-year overall survival for resection compared to LT in patients with a single <3 cm HCC.…”
Section: Management Of Single Small Hcc Liver Transplantation Versusmentioning
confidence: 99%
“…85 In patients without significant fibrosis, resection is universally advised as first-line treatment, but in patients with compensated cirrhosis, recommendations are mixed and vary by tumor size and number. 86 In patients otherwise eligible for LT, postresection 5-year recurrence-free survival is 40%-50%. 87,88 While 10-year overall survival is better with LT for resectable HCC, 89 many studies have shown similar 5-year overall survival for resection compared to LT in patients with a single <3 cm HCC.…”
Section: Management Of Single Small Hcc Liver Transplantation Versusmentioning
confidence: 99%
“…Treatment of early stage HCC is liver resection or transplantation, whereas for patients with BCLS stage B HCC, the recommended treatment is TACE or palliative treatment. However, recent reports suggest surgical treatment can achieve prolonged survival in advanced HCC patients [ 71 , 42 , 72 74 ], even patients with IVC invasion, as occurred in a patient in this series (60 months survival). These findings may justify an aggressive surgical approach and support the use of ALPPS in patients with BCLC stage B HCC.…”
Section: Discussionmentioning
confidence: 59%
“…Hepatic resection seems to be the best therapeutic choice for patients with HCC in normal liver and the preserved liver function allows very large hepatic resections. Three of our cases experienced early recurrence within 15 months after surgery. In two cases, a small recurrent nodule was detected and treated successfully with RFA.…”
Section: Discussionmentioning
confidence: 71%